Comparison of NLC particle sizes derived from SCIAMACHY/Envisat observations with ground-based LIDAR measurements at ALOMAR (69° N) - von Savigny, C.; Robert, C.E.; Baumgarten, G.; Bovensmann, H.; Burrows, J.P. (München : European Geopyhsical Union, 2009)
SCIAMACHY, the Scanning Imaging Absorption spectroMeter for Atmospheric CHartographY has provided measurements of limb-scattered solar radiation in the 220 nm to 2380 nm wavelength range since summer of 2002. Measurements in the UV spectral range are well suited for the retrieval of particle sizes of noctilucent clouds (NLCs) and have been used to compile the largest existing satellite data base of NLC particle sizes. This paper presents a comparison of SCIAMACHY NLC size retrievals with the extensive NLC particle size data set based on ground-based LIDAR measurements at the Arctic LIDAR Observatory for Middle Atmosphere Research (ALOMAR, 69° N, 16° E) for the Northern Hemisphere NLC seasons 2003 to 2007. Most of the presented SCIAMACHY NLC particle size retrievals are based on cylindrical particles and a Gaussian particle size distribution with a fixed width of 24 nm. If the differences in spatial as well as vertical resolution between SCIAMACHY and the ALOMAR LIDAR are taken into account, very good agreement is found. The mean particle size derived from SCIAMACHY limb observations for the ALOMAR overpasses in 2003 to 2007 is 56.2 nm with a standard deviation of 12.5 nm, and the LIDAR observations yield a value of 54.2 nm with a standard deviation of 17.4 nm. publishedVersion